Привілеї польського короля Стефана Баторія для Лоєва 1576 та 1582 рр. - Білоус, Н. (Місто: історія, культура, суспільство, 2018)
У статті розглядаються два привілеї польського короля Стефана Баторія для поліського містечка Лоєв (нині смт, районний центр Гомельської обл., Республіки Білорусь), яке у ХVІ ст. входило до складу Любецького староства Київського воєводства. Ці документи можна вважати цікавими і рідкісними архівними знахідками, досі вони не були опублікованими і запровадженими до наукового обігу. Перший з них – на магдебурзьке право був наданий 3 серпня 1576 р., другий – на лоєвське війтівство для Федора Волка з’явився як доповнення до першого через шість років – 25 листопада 1582 р. Документи походять з архіву князів Сангушків, який тепер зберігається у Державному архіві Польщі в м. Краків (відділення на Вавелі). Ініціатором та отримувачем магдебурзького привілею для Лоєва був Павло Іванович Сапєга, любецький і лоєвський староста з 1560 р. та київський каштелян з 1566 р., який власним коштом розбудовував місто і замок. Привілей на лоєвське війтівство був виданий у 1582 р. Федору Волку в нагороду за його військову службу і участь у бойових діях. Ці документи є винятковими, оскільки за часів правління Стефана Баторія (1576–1586) лише декілька міст у цьому регіоні отримали подібні привілеї. Значення королівських привілеїв для Лоєва було величезне – це була необхідна правова основа і значний поштовх для подальшого його розвитку. Жителі Лоєва отримали самоврядування на засадах магдебурзького права і чимало пільг і вольностей економічного характеру, що вигідно вирізняло їх серед інших міст регіону. The article deals with two privileges of the Polish king Stefan Batory for the Polissya town of Loyew (now the district centre of the Gomel region, the Republic of Belarus). In the 16th century, it was a part of the Liubech starostvo of the Kiev voivodship. The town is known first of all due to military battles that took place in the neighbourhood: July 31, 1649, and during the Second World War, while the pages of its history during the Lithuanian-Polish era, such as the granting of self-government under the Magdeburg law, are still little known. Stefan Batory privileges for Loyew can be considered interesting and rare archival finds, they have not yet been published and introduced into scientific circulation. The first - the Magdeburg Law was granted on August 3, 1576, the second - on the Loyew Vogtship for Fedora Volka appeared as an addition to the first one in six years (November 25, 1582). Unlike the most of the privileges of the time, inscribed in the books of the royal the chancellery, these two were not written in Latin or in Polish, but in Cyrillic. The documents originate from the Archives of the Sangushki princes, which are now stored in the State Archives of Poland in Krakow (Wawel department). The initiator and recipient of the Magdeburg privileges for Loyew was Pavlo Ivanovych Sapiega, Lubeckij and Loyewsky Starosta from 1560, and the Kiev Castellan from 1566. He, at his own expense, built the city and the castle Loyew Mountain, that was lying on the Tartar road and defending the Lithuanian border from the Chernihiv side (which at that time belonged to the Moscow state), and was also protecting the state from the Tatar attacks. The privilege of the Loyew Vogts was granted in 1582 to Fedor Volk as the reward for his military service and participation in hostilities. These documents are exceptional since during the reign of Stefan Batory (1576-1586) only a few cities in this region received similar privileges. The significance of royal privileges for Loyew was enormous – it was a necessary legal basis and a significant impetus for its further development. Residents of Loyew received self-government on the principles of Magdeburg Law and many economic privileges and liberties, which favourably distinguished them among other cities in the region.